Exploring Mediation and Moderation in the Digital Transformation of Culinary SMEs - Nisrina Hamid; Conny (Jurnal Manajemen dan Kewirausahaan, 2025)
This study examines the influence of digital mindset on business performance among culinary MSMEs, with technology adoption as a mediating variable and Need for Stimulation (NST) as a moderating factor, highlighting psychological aspects in the digital transformation of the culinary sector. Employing a quantitative approach and an explanatory research design, data were collected from 125 culinary MSME actors in Kendari City through structured surveys and analyzed using Structural Equation Modeling. The findings reveal that a digital mindset positively affects technology adoption, but does not directly influence business performance; technology adoption serves as a significant mediator. NST was found to negatively moderate the relationship between technology adoption and business performance, indicating that excessive stimulation levels may hinder the effectiveness of technology implementation. This study extends the understanding of Optimal Stimulation Level Theory and emphasizes that while the digital mindset is a crucial prerequisite, it is not the sole determinant of improved business performance. The practical implication suggests the need for digital training programs that consider the psychological characteristics of business actors to enhance the effectiveness of digital transformation. However, the study is limited by its sample and cross-sectional design, and future research is recommended to adopt a longitudinal approach and explore alternative moderating variables.